Foot-rot Disease among Free Living Spotted Deer (Axis Axis) in Bandipur Project Tiger Reserve : Investigation and Control Measures - Yekanthappa, K.; Nanjappa, K. A. (Indian Forester, 1998)
Foot-Rot disease found among free living Spotted Deer (Axis axis) in Bandipur Tiger Reserve has been investigated for the first time. It is caused primarily due to Fusobacteria with secondary infection by Pasteurella species. Prophylactic measures are suggested for controlling the disease.